Patterns of bird song evolution on islands support the character release hypothesis in tropical but not in temperate latitudes. (21st September 2021) - Robert, Aloïs; Melo, Martim; Lengagne, Thierry; Julien, Sacha; Gomez, Doris; Doutrelant, Claire
Abstract: The character release hypothesis—which predicts that a decline in interspecific competition leads to the expansion of trait expression—remains to be tested for communication signals. Taking advantage of the fact that oceanic islands host fewer species than the mainland, we tested whether island birds show an increase in frequency bandwidth of acoustic signals compared with mainland birds. Given the higher animal diversity and more saturated acoustic space in the tropics, we expected acoustic character release, if any, to be stronger in the tropics than in the temperate zone. We field recorded 22 bird species (11 pairs consisting of an endemic island species and its closest mainland relative) breeding at similar latitudes and in similar habitats: six tropical pairs (São Tomé Island/Mount Cameroon) and five temperate pairs (Madeira Island/southern France). For each species, we measured the degree of acoustic interference experienced when vocalizing and the spectral characteristics of its song (minimum and maximum frequencies, bandwidth). As expected, island species spent more time vocalizing alone, and any overlap in vocalizations involved fewer species. The vocalizations of island species spanned broader frequency bandwidths than their mainland counterparts in the tropics (true for all six pairs), but this pattern was less evident in the temperate region (2/5 pairs with no marked differences and 1/5 with opposite pattern). Overall, the character release of communication signals only occurred where the differential in number of species was large (tropics). We discuss latitude differences and the potential factors driving the observed differences.